Household expectations and dissent among policymakers - Grebe, Moritz; Tillmann, Peter; Justus Liebig University Giessen (My University, 2025)
This paper studies the impact of dissent in the ECB’s Governing Council on uncertainty surrounding households’ inflation expectations. We conduct a randomized controlled trial using the Bundesbank Online Panel Households. Participants are provided with alternative information treatments concerning the vote in the Council, e.g. unanimity and dissent, and are asked to submit probabilistic inflation expectations. The results show that the vote is informative. Households revise their subjective inflation forecast after receiving information about the vote. Information about unanimity or dissent causes a wider individual distribution of future inflation for those households that were relatively certain before the treatment. For the remaining 60% of households, this information reduces uncertainty. Information about dissent increases uncertainty more than information about a unanimous vote, though the difference is not statistically significant. A unanimous vote unambiguously reduces inflation uncertainty for households with anchored inflation expectations.
Keywords: ddc:330